Increasing online Purchase through Perceived Usefulness, Perceived Risk and Perceived Ease of Use - Lena Ellitan; Cornelia Prayogo (CV. Ulil Albab Corp, 2022)
The rapid development of internet users or users is due to the support of mobile phone technology and smooth mobile network connections, meaning that when cellphones can access the internet easily, internet users will develop quickly. This not only affects the community as consumers, but also affects business people to take advantage of the development of internet users, namely by doing trading business in the form of electronic stores so that e-commerce is also growing rapidly. Perceived usefulness, subjective norms, and enjoyment as predictors of online shopping behavior. Interest in online shopping is also influenced by perceived risk, namely the fear of consumers to accept risk in online shopping and perceived ease of use, namely consumer perceptions of the ease of use of online sites. This paper will discuss the role of perceived usefulness (PU), perceived risk (PR) and perceived ease of use (PEU) in influencing online purchases.